Lack of Hypoxia Inducible Factor-1α Influences on Macrophages Ability to Deal with Leishmania braziliensis In Vitro and Affects Pathology In Vivo - Rodrigo C.O. Sanches; Leonardo G. Vaz; Fabio V. Marinho; Erika S. Guimarães; Edgar M. Carvalho; Lucas P. Carvalho; Sergio C. Oliveira (JID Innovations)
Cutaneous leishmaniasis, caused by Leishmania braziliensis, still represents a serious health problem in Brazil, especially in the northeast region. Currently, to our knowledge, no report describes the role of hypoxia inducible factor-1α (HIF-1α) during L braziliensis infection. In this study, we demonstrated that the parasite induces HIF-1α expression and stabilization in bone marrow–derived macrophages only when added with exogenous IFN-γ plus lipopolysaccharide. Coherently, we did not find an enrichment in the glycolytic pathway upon bone marrow–derived macrophage infection. Evaluating the impact of HIF-1α absence during macrophage infection in vitro, we observed HIF-1α–knockout cells present at high levels of IL-10, reduced production of nitric oxide, and decreased expression of VEGF-A. As a result, parasite viability improves within HIF-1α–knockout cells. However, in vivo, the absence of myeloid cells expressing HIF-1α had no influence on nitric oxide at tissue levels and in parasite burden. Conversely, lack of HIF-1α significantly affects L braziliensis–induced pathology. Ear lesions induced in myeloid HIF-1α–knockout mice were thicker, presenting higher frequency of macrophages, neutrophils, CD4+, and CD8+ T cells as well as higher levels of IL-12, IL-1β, and IFN-γ, compared with those in wild-type mice. Moreover, draining lymph nodes from myeloid HIF-1α–knockout mice also harbored increased populations of T cells. Our data demonstrate that HIF-1α plays an important role during L braziliensis infection influencing skin pathology in vivo.